2018
DOI: 10.3233/thc-170862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Cardio First AngelTM on chest compression performance

Abstract: Chest compression as performed by laymen was significantly improved with regard to compression depth when using the CFA for guidance and feedback. With the device, no cases of incorrect hand positioning occurred in any group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…One subsequent clinical trial ( n = 80) using the CFA device reported improved ROSC rates when compared to standard manual compressions [7]. This was followed by simulation studies using laypersons that showed improved hand position, mean compression depth, rate, and compression fraction with the CFA device [20, 21]. Several other non-AED compression feedback devices have shown promising results in simulation studies but lack clinical testing [7, 15, 16, 18, 22, 32].…”
Section: Discussionmentioning
confidence: 99%
“…One subsequent clinical trial ( n = 80) using the CFA device reported improved ROSC rates when compared to standard manual compressions [7]. This was followed by simulation studies using laypersons that showed improved hand position, mean compression depth, rate, and compression fraction with the CFA device [20, 21]. Several other non-AED compression feedback devices have shown promising results in simulation studies but lack clinical testing [7, 15, 16, 18, 22, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that more than 90% of CCs using feedback devices were delivered in the correct position [2][3][4][5]. However, these studies used the Resusci Anne Skill Reporter Manikin ™ (Laerdal Medical Corporation, Stavanger, Norway), which has a 10 × 10 cm 2 plate on the back of the chest, or the Ambu ® Man Torso (Ambu A/S, Ballerup, Denmark) CPR manikin, which has a 9 × 6 cm 2 plate on the back of the chest.…”
Section: Discussionmentioning
confidence: 99%
“…The 2020 International Consensus guidelines recommend the use of a feedback device for cardiopulmonary resuscitation (CPR) training [1] to facilitate effective CPR based on the evaluation of its components, including compression depth, compression rate, chest wall recoil, and interruption time [2][3][4][5][6]. Some clinical studies demonstrated that CPR depth and rate were significantly estimated better with a feedback device [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several community intervention trials have examined ways to improve bystander CPR rates 34–41. Some of these have focused on improving CPR training and others on the quality of CPR technique 34–36.…”
Section: Introductionmentioning
confidence: 99%
“…Several community intervention trials have examined ways to improve bystander CPR rates 34–41. Some of these have focused on improving CPR training and others on the quality of CPR technique 34–36. Other successful strategies to increase bystander CPR rates include dispatch of lay and/or professional voluntary responders by emergency services and use of apps to activate trained citizens and off-duty paramedics and doctors 42–46.…”
Section: Introductionmentioning
confidence: 99%